Detection of SARS-Cov-2 N-protein in Mesenchymal Cells of Umbilical Warton’s Jelly in Women with COVID-19 - Nizyaeva, N.V.; Lomova, N.A.; Dolgopolova, E.L.; Karapetyan, T.E.; Petrova, U.L.; Shmakov, R.G.; Frankevich, V.E. (Biomedical Chemistry: Research and Methods, 2022)
Despite the large number of studies on the new coronavirus infection SARS-Cov-2 characterized by vascular damage on the impact of the virus on the mother-placenta-fetus system remains unknown. The umbilical cord, according to its functional purpose, is a complex of vessels protected from external influences by the embryonic connective tissue –Wharton’s jelly. The aim of the study was to detect the structural components of SARS-Cov-2 in the histological structures of umbilicals cord in patients with COVID-19 in the tissues of the umbilical cord of women with COVID-19. The main group included 40 pregnant women who were treated at the academician V. I. Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology (March-April 2020) with a confirmed diagnosis of COVID-19 (according to the positive PCR test of a nasopharyngeal swab) and 40 pregnant women of the comparison group, without clinical symptoms and laboratory tests, including the negative PCR test. As a result of the immunohistochemical study of the umbilical cord with primary antibodies to the SARS-Cov-2 N-protein in the COVID-19 group, staining of the cytoplasm of fibroblast-like cells and single macrophages Wharton’s jelly was detected (p<0.05). In the group of women without coronavirus infection no staining in Wharton’s jelly cells was detected. The probable persistence of viral particles in mesenchymal cells and macrophages of the Wharton’s jelly in the umbilical cord can be important for establishment new aspects of influence COVID-19 on the mother-placenta-fetus system. Our results suggesting persistence of COVID-19 viral proteins in mesenchymal cells of the umbilical cord could be an important in establishing new pathogenic mechanisms for the fetal protection against viruses.